Potential Islamic Radicalism and Terrorism in the Province of West Nusa Tenggara - Muhammad Harfin Zuhdi (AHKAM : Jurnal Ilmu Syariah, 2019)
Studies on the root and causes of radicalism and terrorism have revealed that economic drawbacks and injustice are the primary causes of the birth of such groups. However, it is likely that it would be a distinct case within the Indonesian landscape, particularly West Nusa Tenggara Province (NTB), given the relative conduciveness and good democratic atmosphere of the country and province. For this reason, drawing on the available artefacts and several mass conflicts and terrors happening in the province, this study analyses whether there is any potential of radical and terrorist groups to grow; and, if any, what factors promoting such growth. The findings indicate that the province can be a potential area for radical and terrorist groups to thrive. Furthermore, the main factors promoting the growth of such radical groups and violence or mass incidents include: the misinterpretation of the Islamic teachings, the available network of terrorist groups such as East Indonesian Mujahidin in the province, the geographical location, and the reluctance of the mainstream moderate Muslims to promote religious moderatism to such growing groups in both islands of Sumbawa and Lombok.  Penelitian ini menjelaskan akar dan penyebab radikalisme dan terorisme di Provinsi Nusa Tenggara Barat (NTB). Selama ini diungkapkan  bahwa keterbelakangan ekonomi dan ketidakadilan adalah penyebab utama lahirnya kelompok radikal dan teroris tersebut. Namun,  kasus berbeda terdapat di Nusa Tenggara Barat (NTB), karena di daerah ini suasana kondusif dan demokrasi yang relatif baik. Untuk  itu,  dengan melihat fenomena tersebut dan beberapa konflik massa dan teror yang terjadi di provinsi ini, penelitian ini menganalisis apakah ada potensi kelompok radikal dan teroris untuk tumbuh; dan, jika ada, faktor apa yang mendorong pertumbuhan tersebut. Temuan penelitian menunjukkan bahwa provinsi ini dapat menjadi daerah pontensial bagi kelompok radikal dan teroris untuk berkembang. Hal ini disebabkan karena salah tafsir atas ajaran Islam oleh jaringan kelompok teroris yang seperti Mujahidin Indonesia Timur selain lokasi geografinya. Alasan lainya ialah keengganan kaum Muslim moderat untuk memberi kesadaran terhadap kelompok-kelompok teroris di provinsi tersebut.